IMPLEMENTASI SISTEM INTERNET OF THINGS SEBAGAI INPUT DATA REALTIME PADA SMART SECURITY COVID-19 - Intan Putri Gemilang; Rahmat Hidayat; Lela Nurpulaela (Politeknik Harapan Bersama Tegal, 2021)
Abstrak - COVID-19 (Corona Virus Disease 2019) has hit the whole world, including Indonesia. The public is advised by the government to implement health protocols to reduce the level of spread of the corona virus. Although mobility is very limited, there are still many people who carry out activities outside the home. So to avoid the increase in the number of positive cases of COVID-19, it is necessary to increase the security protocol against COVID-19 in public service places. In addition, the public needs to be provided with information about the development of the spread to education in dealing with COVID-19. This is necessary because there are still many people who don't care by not complying with health protocols or acting in excessive panic such as buying masks and disinfectants in large quantities only for personal interests. This is not only detrimental to themselves but also to others, one of which is the medical staff who need PPE (Personal Protective Equipment) more difficult to get it because it is sold out in the market due to people's mistakes in responding to the pandemic due to lack of education which is then used by people who are not aware of it. responsible for personal gain. Therefore, to overcome this problem, a COVID-19 Smart Security product was created that can check temperature and spray disinfectants automatically. The temperature checking system is connected to the Internet of Things to monitor visitor temperature data in real time and can provide education about COVID-19. Data from the device will be sent to the NodeMCU ESP8266 which is a microcontroller equipped with WIFI ESP8266 as an IoT platform. Then after the data is received by the NodeMCU ESP8266, the data will be sent back to a website to be visualized in graphic form as an analysis of the development of COVID-19 in an area.